M2 Macrophages promote IL-33 expression, ILC2 expansion and mucous metaplasia in response to early life rhinovirus infections - Han, Mingyuan; Breckenridge, Haley A.; Kuo, Shiuhyang; Singh, Shilpi; Goldsmith, Adam G.; Li, Yiran; Kreger, Jordan E.; Bentley, J. Kelley; Hershenson, Marc B. (Frontiers in Immunology, 2022)
Wheezing-associated rhinovirus (RV) infections are associated with asthma development. We have shown that infection of immature mice with RV induces type 2 cytokine production and mucous metaplasia which is dependent on IL-33 and type 2 innate lymphoid cells (ILC2s) and intensified by a second heterologous RV infection. We hypothesize that M2a macrophages are required for the exaggerated inflammation and mucous metaplasia in response to heterologous RV infection. Wild-type C57Bl/6J mice and LysMCre IL4Rα KO mice lacking M2a macrophages were treated as follows: (1) sham infection on day 6 of life plus sham on day 13 of life, (2) RV-A1B on day 6 plus sham on day 13, (3) sham on day 6 and RV-A2 on day 13, or (4) RV-A1B on day 6 and RV-A2 on day 13. Lungs were harvested one or seven days after the second infection. Wild-type mice infected with RV-A1B at day 6 showed an increased number of Arg1- and Retnla-expressing lung macrophages, indicative of M2a polarization. Compared to wild-type mice infected with RV on day 6 and 13 of life, the lungs of LysMCre IL4Rα KO mice undergoing heterologous RV infection showed decreased protein abundance of the epithelial-derived innate cytokines IL-33, IL-25 and TSLP, decreased ILC2s, decreased mRNA expression of IL-13 and IL-5, and decreased PAS staining. Finally, mRNA analysis and immunofluorescence microscopy of double-infected LysMCre IL4Rα KO mice showed reduced airway epithelial cell IL-33 expression, and treatment with IL-33 restored the exaggerated muco-inflammatory phenotype. Conclusion: Early-life RV infection alters the macrophage response to subsequent heterologous infection, permitting enhanced IL-33 expression, ILC2 expansion and intensified airway inflammation and mucous metaplasia.